A Comprehensive Review of Self-Assembled Monolayers as Hole-Transport Layers in Inverted Perovskite Solar Cells - Yuchen Yuan; Houlin Li; Haiqiang Luo; Yang Zhang; Xiaoli Li; Ting Jiang; Yajie Yang; Lei Liu; Baoyan Fan; Xia Hao (Energies)
The hole-transport layer (HTL) plays a pivotal role in engineering high-performance inverted perovskite solar cells (PSCs), as it governs both hole extraction/transport dynamics and critically impacts the crystallization quality of the perovskite absorber layer in device architectures. Recent advancements have highlighted self-assembled monolayers (SAMs) as promising candidates for next-generation HTL materials in inverted PSCs due to their intrinsic advantages over conventional counterparts. These molecularly engineered interfaces demonstrate superior characteristics including simplified purification processes, tunable molecular structures, and enhanced interfacial compatibility with device substrates. This review systematically examines the progress, existing challenges, and future prospects of SAM-based HTLs in inverted photovoltaic systems, aiming to establish a systematic framework for understanding their structure–property relationships. The review is organized into three sections: (1) fundamental architecture of inverted PSCs, (2) molecular design principles of SAMs with emphasis on head-group functionality, and (3) recent breakthroughs in SAM-engineered HTLs and their modification strategies for HTL optimization. Through critical analysis of performance benchmarks and interfacial engineering approaches, we elucidate both the technological merits and inherent limitations of SAM implementation in photovoltaic devices. Furthermore, we propose strategic directions for advancing SAM-based HTL development, focusing on molecular customization and interfacial engineering to achieve device efficiency and stability targets. This comprehensive work aims to establish a knowledge platform for accelerating the rational design of SAM-modified interfaces in next-generation optoelectronic devices.